Automatic pot/ wok stirring machine / Nurul Fatihah Muhamad Miftahuddin - Muhamad Miftahuddin, Nurul Fatihah (2024)
Based on the engineering calculations and analyses, I can infer that the product is only partially complete. With the evidence I have, this project can move on to the fabrication phase. By assembling all of the resources that have been created, this project can be completed without any issues. The manufacturing process will be utilized to assess whether the product meets the requirements of the proposal or not. The product is complete by the next semester, all the objectives being complete. This product suggestion is finished. As the name “stirrer cooking machine" suggests, it cooks meals less usage of labor cost. The primary goal is to simplify, expedite, and simplify the process of cooking. You just need to select the recipe you want to eat, prepare the ingredients and the machine will begin stirrer and was added it step by step and alert you when it is ready when smells good. It will come pre-loaded with your choice of recipes, and the quantity of ingredients will be defined according the recipe